Predicting attitude towards performance enhancing substance use: A comprehensive test of the Sport Drug Control Model with elite Australian athletes - Jalleh, G.; Donovan, R. J.; Jobling, I. (Journal of Science and Medicine in Sport, 2014)
Objectives: This study presents a comprehensive examination of the Sport Drug Control Model via survey data of elite Australian athletes. Design: A cross-sectional nationwide mail survey. Methods: A mail survey of 1237 elite Australian athletes was conducted. Structural equation modelling was employed to test the model. Results: Morality (personal moral stance on performance-enhancing substances use), reference group opinion (perceived moral stance of reference group on performance-enhancing substances use) and legitimacy (perceptions of the drug testing and appeals processes) evidenced significant relationships with attitude towards performance-enhancing substances use, which in turn was positively associated with doping behaviour. The model accounted for 81% and 13% of the variance in attitude towards performance-enhancing substances use and doping behaviour, respectively. Conclusions: These findings validate the usefulness of the Sport Drug Control Model for understanding influences on performance-enhancing substances use. Nevertheless, there is a need to survey athletes representing a broader range of competition levels and cross-cultural research to test the model's applicability to other populations of athletes.